2019
DOI: 10.1111/exd.13933
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of circadian human facial surface lipid composition

Abstract: Background The circadian rhythm is an endogenous clock that governs a wide range of physiological functions. In the skin, rhythmic changes in skin barrier function have been investigated at the physiological level; however, few studies at the molecular level have been reported. Additionally, there is no study on lipidomic profile variations of skin surface lipid (SSL), which could potentially explain the rhythmic changes in skin status. Objectives The SSL profile of healthy young women was analysed to assess S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…1); high levels of unsaturated FFAs may cause barrier disorders and are associated with inflammation and with thickening of the follicle stem cells in acne. 7 These results are also consistent with our previous work showing that ceramide chains are shorter and levels of unsaturated FFAs are higher in young men with acne than in young men without acne. 2 However, surprisingly, we found that relative ceramide levels in patients with IA were higher than those in patients without IA (Fig.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…1); high levels of unsaturated FFAs may cause barrier disorders and are associated with inflammation and with thickening of the follicle stem cells in acne. 7 These results are also consistent with our previous work showing that ceramide chains are shorter and levels of unsaturated FFAs are higher in young men with acne than in young men without acne. 2 However, surprisingly, we found that relative ceramide levels in patients with IA were higher than those in patients without IA (Fig.…”
supporting
confidence: 93%
“…Additionally, the amount of unsaturated FFAs present in the sebum of patients with IA was higher than in patients without IA (Fig. ); high levels of unsaturated FFAs may cause barrier disorders and are associated with inflammation and with thickening of the follicle stem cells in acne . These results are also consistent with our previous work showing that ceramide chains are shorter and levels of unsaturated FFAs are higher in young men with acne than in young men without acne .…”
supporting
confidence: 90%
“…Additional, they might be used in food or other products for the efficacy of inhibiting bacteria 21,22 . The above results showed that VTE and DMY have great potential as food additives in food industry and so on 23 . The total protein expression + 15.5 + 9.9…”
Section: Resultsmentioning
confidence: 68%
“…Under normal conditions, the skin surface lipid (SSL) components are distributed in certain proportions between the skin surface and stratum corneum to maintain the skin's healthy condition. Changes in the total amount of skin surface lipids, or the increase or decrease in the amount of any components therein, will affect the skin barrier function 3,12,13 …”
Section: Fatty Acid Metabolism In Skin Surface Lipidsmentioning
confidence: 99%